2019
DOI: 10.35295/osls.iisl/0000-0000-0000-1031
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Interaction of Judicial Objectivity

Abstract: Like other Western legal systems, the Swedish legal system constructs objectivity as an unemotional state of being. We argue that the enactment of objectivity in situ relies on objectivity work including emotion management and empathy. Building on qualitative interviews and observations in Swedish district courts, we analyse courtroom interaction through a dramaturgical lens, highlighting tacit signals and interprofessional emotional communication aimed to secure objective procedures, while sustaining the idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This often requires what Bergman Blix and Wettergren describe as 'skillful inter-professional emotional attuning'. 124 The same authors use the concept of 'objectivity work' to explain the nature of neutrality among differing courtroom actors. 125 For example, they argue that adjudication requires judges to emphasize their neutral demeanour, whereas prosecutors experience a 'contingent and shifting' objectivity due to their case involvement and interaction with witnesses.…”
Section: Reconceptualizing Neutralitymentioning
confidence: 99%
“…This often requires what Bergman Blix and Wettergren describe as 'skillful inter-professional emotional attuning'. 124 The same authors use the concept of 'objectivity work' to explain the nature of neutrality among differing courtroom actors. 125 For example, they argue that adjudication requires judges to emphasize their neutral demeanour, whereas prosecutors experience a 'contingent and shifting' objectivity due to their case involvement and interaction with witnesses.…”
Section: Reconceptualizing Neutralitymentioning
confidence: 99%
“…However, one foundation for arriving at a correct legal judgment is that the different parties are unconnected and independent, making social solidarity a complex issue. On the one hand, legal professionals need to share a moral order if they are to agree on how decisions should be made and to collaborate in moving a case forward (Barbalet 2002; Bergman Blix and Wettergren 2019a); on the other hand, independence in decision‐making is fundamental both constitutionally (top‐down) and in interactional practice (bottom‐up) 5…”
Section: Rational Emotions In a Legal Decision‐making Processmentioning
confidence: 99%
“…Even though they play conflicting roles, argue for or take conflicting decisions, they depend on each other when processing a case through the bounded IRC. Previous research has shown that this requires emotional attunement and situated empathy, interprofessionally as well as with laypeople (Bergman Blix and Wettergren 2019a; Roach Anleu and Mack 2005), but it may also trigger irritation and anger when the other participants fail to collaborate (Maroney 2012). This is by no means a complete list of the emotions linked to the legal interaction order; instead, it provides a taxonomy for understanding the mechanisms of a collective rational ritual.…”
Section: Rational Emotions In a Legal Decision‐making Processmentioning
confidence: 99%
“…But it may also be rooted in the assumption underpinning much of Western legal culture to this day that judicial work and the act of judgment must be done from a rational, objective stance and cannot be shaped or influenced by emotions. Bergman Blix and Wettergren (2019) call this ‘positivist objectivity’, an ideal that has been largely criticized within the social sciences although it still holds a strong influence in the field of the law. According to this positivist notion, judicial decision-makers must free themselves ‘from all physical and social affiliations and acquire knowledge through independent empirical observations and evidence’ by using pure or instrumental rationality.…”
Section: Emotions Judgment and Tjmentioning
confidence: 99%
“…This verbal ‘working through’ was not surprising to us as in the Argentine context psychoanalysis is a widespread and common practice (Plotkin, 2002). At the same time, the emotional and performative work (Bergman Blix and Wettergren, 2019) that goes into concealing these experiences throughout the public hearings in the courtroom highlight the stakes inherent in these trials.…”
Section: Emotions and The Everyday Work Of Justicementioning
confidence: 99%